2020
DOI: 10.1111/acer.14431
|View full text |Cite
|
Sign up to set email alerts
|

Opioid and Dopamine Genes Interact to Predict Naltrexone Response in a Randomized Alcohol Use Disorder Clinical Trial

Abstract: Background: While the opiate antagonist, naltrexone, is approved for treating alcohol use disorder (AUD), not everyone who receives the medication benefits from it. This study evaluated whether the OPRM1 SNP rs1799971 interacts with the dopamine transporter gene DAT1/SLC6A3 VNTR rs28363170 or the catechol-O-methyltransferase (COMT) gene SNP rs4680 in predicting naltrexone response. Methods: Individuals who met DSM-IV alcohol dependence were randomly assigned to naltrexone (50 mg/d) or placebo based on their OP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 69 publications
(89 reference statements)
0
9
0
Order By: Relevance
“…We initially reported that, among non-treatment-seeking AUD individuals, naltrexone, relative to placebo, reduced alcohol self-administration and cue-elicited ventral striatal activation most among OPRM1 G-allele carriers who were also SLC6A3 10R homozygotes ( 5 , 6 ). We subsequently replicated and extended this finding in a randomized controlled trial (RCT) among treatment-seeking AUD patients, in which naltrexone, relative to placebo, most effectively reduced heavy drinking among OPRM1 G-allele carriers who were also SLC6A3 10R or COMT val-allele homozygotes ( 7 ). Taken together, these data suggested that a combination of genetically predisposed enhanced MOR function and reduced striatal or cortical synaptic dopamine accumulation was associated with superior naltrexone response.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…We initially reported that, among non-treatment-seeking AUD individuals, naltrexone, relative to placebo, reduced alcohol self-administration and cue-elicited ventral striatal activation most among OPRM1 G-allele carriers who were also SLC6A3 10R homozygotes ( 5 , 6 ). We subsequently replicated and extended this finding in a randomized controlled trial (RCT) among treatment-seeking AUD patients, in which naltrexone, relative to placebo, most effectively reduced heavy drinking among OPRM1 G-allele carriers who were also SLC6A3 10R or COMT val-allele homozygotes ( 7 ). Taken together, these data suggested that a combination of genetically predisposed enhanced MOR function and reduced striatal or cortical synaptic dopamine accumulation was associated with superior naltrexone response.…”
Section: Introductionmentioning
confidence: 76%
“…Detailed methods for the parent RCT ( ClinicalTrials.gov identifier: NCT00920829 ) have been reported previously ( 7 , 27 ). The Medical University of South Carolina Institutional Review Board approved all procedures, and all participants provided informed consent before participation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since its publication, the DSM-5 SUD diagnostic criteria have been widely adopted by clinicians and researchers to assess risk factors and consequences of substance use, and to identify participants for inclusion in clinical trials of treatment effectiveness. Nevertheless, a wide variety of researchers continue to rely on DSM-IV diagnoses because data from many studies, including large clinical trials [18,[22][23][24][25][26] and U.S yearly national general population surveys are based on DSM-IV diagnoses of SUD [27].…”
Section: Introductionmentioning
confidence: 99%